Electrochemical sensor based on reduced graphene oxide and molecularly imprinted poly(phenol) for D-xylose determination - Pompeu Prado Moreira, Luiz Felipe [UNESP] (2020)
The present work reports the development of an electrochemical sensor based on molecularly imprinted polymer for the determination of D-xylose. This is the first report of its kind in the literature. The sensor was prepared through the modification of a glassy carbon electrode with reduced graphene oxide and molecularly imprinted poly(phenol) film. The use of graphene oxide and molecularly imprinted poly(phenol) film led to remarkable improvements in the sensor sensitivity and selectivity, respectively. The electrode was characterized by several techniques, including cyclic voltammetry, differential pulse voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy, atomic force microscopy and RAMAN spectroscopy. The proposed sensor presented linear responses ranging from 1.0 × 10−13 to 1.0 × 10−11 mol L−1. The amperometric sensitivity, limit of detection, and limit of quantification obtained were 6.7 × 105 A L mol−1; 8.0 × 10−14 mol L−1 and 2.7 × 10−13 mol L−1 (n = 3), respectively. The proposed analytical method was successfully applied in sugarcane bagasse, which is known to contain large amounts of D-xylose and other structurally similar molecules in its composition. The chemical composition of sugarcane bagasse makes this biomass suitable for evaluating the ability of the sensor to specifically detect the target molecule. Mean recoveries obtained in the analysis ranged from 95.4 to 105.0%; this indicates that the proposed method has good accuracy when applied toward the determination of D-xylose.